DEKLARASI BALFOUR : TRAGEDI BAGI BANGSA PALESTINA DALAM PUISI-PUISI ARAB TAHUN 1920-1948 - Hindun Hindun (CMES (Center of Middle Eastern Studies), 2018)
The arrival of Jews in Palestine since 1882 changed the order of life of the Palestinian people. Jews began to buy land from Palestinians with the aim of mastering all Palestinian land in the future. This mastery is carried out to realize the ideals of establishing a Jews country that has been proclaimed by The World Zionist Organization. The achievement of control of Palestinian land became apparent when the Ottoman Government in Palestine was defeated and turned into British hands. In 1917, Britain gave way to the Zionist Organization by signing the Balfour Declaration which gave permission to them to make Palestine a homeland. In three decades, the Zionist Organization succeeded in annexing Palestine and making it a Jewish state called Israel. The establishment of the state of Israel became a tragedy to the Palestinians. Arab poets have resisted since the signing of the Balfour Declaration until the tragedy of Israel's annexation of Palestine with their poems. Literary works, in the theory of adab almuqawamah, were written to arouse the spirit of resistance of a nation against colonialism. Arab poets through their poems warn of the adverse consequences of the Balfour Declaration for Palestine. Their poetry is also to arouse the fighting spirit of the Palestinian people against Israel.